IMPLEMENTASI PROGRAM PENYULUHAN BENCANA DAERAH DALAM RANGKA MENINGKATKAN KESADARAN MASYARAKAT OLEH BADAN PENANGGULANGAN BENCANA DAERAH DI KABUPATEN SUMEDANG - Suherman (LPPM UNSAP & FISIP UNSAP, 2024)
This research aims to find out how the Disaster Education Program is implemented in order to increase public awareness in Sumedang Regency, what factors hinder it and how to overcome the obstacles. The research method used in the research is qualitative methodology. With research informants, namely five informants. The data collection techniques used were literature study and field study consisting of observation, interviews and documentation. Meanwhile, the processing procedures in this research are data reduction, data presentation, data verification and triangulation. Based on the research results, it was concluded that the Disaster Outreach Program in the Context of Developing the Basic Capabilities of Poor Communities in Sumedang Regency can be said to be quite good, but there are still several obstacles. This occurs because of obstacles such as the lack of public understanding of the disaster education program, internal human resources are still small, the budget is limited, facilities and infrastructure are still lacking and there is a lack of expert staff. At the end of writing this research, the researcher provides suggestions, namely that BPBD is more active in conducting outreach, counseling and simulations to the community.